Esophageal-Pleural Fistula after Intraoperative Transoesophageal Echocardiography in A Patient with Enlarged Left Atrium (Global Journal of Medical Research, 2023)
After mitral valve replacement in an 81-year-old woman there was evidence of an important communication between the esophagus and the right pleura Diagnosis was confirmed with Oral Gastrografin radiography and esophagoscopy Thoracic computed tomography scans better indicated fistula location and extension but also showed the close relationship and the compression of huge left atrium on the oesophagus Our hypothesis was that the lesion was induced by transoesophageal echocardiography probe in a favourable setting An enlarged left atrium should be recognized as a risk factor for TEE-induced esophageal perforation especially in fragile patients with marked esophagus distortion
Keywords: esophageal fistula; pleural fistula; transoesophageal echocardiography; left atrium